The economic model of Chinese shopping centres in Europe - Li Minghuan (M@ppemonde)
Starting at the turn of the 21st century, Chinese shopping centres have rapidly developed in Europe’s major cities. Be it Paris, Rome, Madrid or Moscow, these centres, through the spatial concentration of shops, have become one of the modalities of China’s presence abroad. This article retraces the historical and social contect that has contributed to the development of Chinese shopping centres in Europe. It then offers a typology of these centres according to their characterisitics. Finally, it outlines the social challenges and problems facing these centres in the European context during the aftermath of the 2008 economic crisis.